Ozonation process and water disinfection. Issue 6 (21st December 2018) - Nghi, Nguyen Hoang; Cuong, Le Cao; Dieu, Tran Vinh; Ngu, Tu; Oanh, Doan Thi Yen
Abstract: As commonly known, ozone is a highly effective disinfectant for both aqueous and gaseous media. It works through oxidation. Dissolved ozone causes the increases of the redox potential ORP of water. During the ozonenation process, the time‐dependent redox potential ORP of water depends strongly on the density of microbes in it. By analyzing the time‐dependent redox potential, it is possible to measure and calculate the parameters such as the oxidizing rate, the maximal redox potential ORPmax etc. of the ozonated water. These parameters of water reflect the microbiological pollution level of water. Ozonated water having a certain ORP level obtains disinfecting ability. Bacteriological analysis of the water samples after ozonation show that total coliform and E. coli bacteria were fully removed after a few minutes at ORP of 800 mV.